Isoperimetric problems of the calculus of variations with fractional derivatives - Almeida, Ricardo (2013)
In this article, we study isoperimetric problems of the calculus of variations with left and right Riemann-Liouville fractional derivatives. Both situations when the lower bound of the variational integrals coincide and do not coincide with the lower bound of the fractional derivatives are considered.